2020
DOI: 10.1017/ice.2020.1335
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coronavirus disease 2019 (COVID-19) response on central-line–associated bloodstream infections and blood culture contamination rates at a tertiary-care center in the Greater Detroit area

Abstract: A comparative retrospective study to quantify the impact of Coronavirus Disease 2019 (COVID-19) on patient safety. We found a statistically significant increase in central line-associated blood stream infections and blood culture contamination rates during the pandemic. Increased length of stay and mortality was also observed during COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 7 publications
3
53
1
3
Order By: Relevance
“… 18 Another study found that both CLABSI and blood culture contamination rates increased during the pandemic. 19 The IPs in this study noted several factors they believed contributed to the increase in HAIs, including frequently changing protocols, staff turnover, lack of resources for training new staff, and visitor restrictions. Some IPs also described an increased placement of femoral central lines, which could increase risk for CLABSI.…”
Section: Discussionmentioning
confidence: 79%
“… 18 Another study found that both CLABSI and blood culture contamination rates increased during the pandemic. 19 The IPs in this study noted several factors they believed contributed to the increase in HAIs, including frequently changing protocols, staff turnover, lack of resources for training new staff, and visitor restrictions. Some IPs also described an increased placement of femoral central lines, which could increase risk for CLABSI.…”
Section: Discussionmentioning
confidence: 79%
“…The most J o u r n a l P r e -p r o o f frequent microorganisms, as expected, were Staphylococcus aureus, Enterococcus spp., Escherichia coli, and Pseudomonas aeruginosa 24 . The infections frequently involved multidrug-resistant microorganisms [25][26][27][28][29] Surprisingly, and despite overuse of antibiotics during the pandemic, preliminary data suggest that the incidence of Clostridioides difficile infection decreased in COVID cases [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Our series includes 81 patients with proven CR-BSIs and compared a similar time period in 2019 and 2020, we found that the frequency of CR-BSI increased 3-fold during the COVID period. Very recently, Le Rose et al 30 reported an increase in the incidence of vascular catheter-related infections during the pandemic. The authors analyzed a series of bloodstream infections, with no clear portal of entry, that they related with central-line associated bloodstream infection (CLABSI).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations